Design of the American Wake Experiment (AWAKEN) field campaign. Issue 2 (1st May 2022) - Debnath, Mithu; Scholbrock, Andy K.; Zalkind, Daniel; Moriarty, Patrick; Simley, Eric; Hamilton, Nicholas; Ivanov, Chris; Arthur, Robert S.; Barthelmie, Rebecca; Bodini, Nicola; Brewer, Alan; Goldberger, Lexie; et al.
Abstract: The American WAKE experimeNt (AWAKEN) is a multi-institutional collaborative field campaign, starting in March 2022, that will gather an unprecedented data set including both atmospheric observations and wind plant operational data. This comprehensive data set will be used to characterize the wind plant performance and turbine loading in different operational and atmospheric conditions and validate the use of different wind plant control strategies and simulation frameworks. An extensive field campaign like AWAKEN requires proper coordination and long-term planning to be successful. In this paper, we review the major activities planned during AWAKEN to provide information for current and future project partners. Specifically, we provide information about the project sites, their planned instruments, and how these will relate to the scientific objectives of the overall AWAKEN project.